The nutraceuticals: a new therapeutic strategy in the management of digestive and respiratory disorders - Ciprandi, Giorgio; Aragona, Salvo Emanuele; Drago, Lorenzo; La Mantia, Ignazio (Acta Biomedica Atenei Parmensis, 2019)
Nutraceuticals represents an intriguing challenge in clinical practice. They are currently used worldwide in all fields of Medicine. The present Supplement reports two Italian surveys concerning a probiotic mixture employed in patients with chronic intestinal disorders and a Medical Device used in patients with upper respiratory diseases. These surveys were conducted on a group of Italian gastroenterologists and on a group of Italian otolaryngologists respectively. Both surveys demonstrated that these compounds may represent a useful therapeutic option in clinical practice.